Testando o CAPM no mercado acionário brasileiro utilizando GARCH Multivariado entre 1995 e 2012 - Godeiro, Lucas Lúcio (2012)
The work aim to test the CAPM for the Brazilian Shares Market using the static was beta and the dynamic beta. The sample used is composed for 28 shares of the Ibovespa index in March 21, 2012 and that was traded long the period researched, between 01/01/1995 and 20/03/2012. Was estimated the static and dynamic betas, and that the dynamics betas has a larger explication power on the cross section returns excess. It was found that the parameters that measure relative risk aversion were significant, indicating that an increase in volatility negatively affects the expected return of the agents